Efforts of the Al-Istiqomah Community Reading Garden Management in Increasing the Reading Interest of Primary Education-Age Children - Muhammad Aditya Firdaus; Maman Suherman; Eva Bella Nuarida; Eli Endrawati; Hendri Abdul Qohar; Agus Ruswandi (Universitas Muhammadiyah Enrekang, 2025)
Reading interest among primary school-aged children has become critical in Indonesia's education field. One initiative to foster children's interest in reading is the Community Reading Gardens (Taman Bacaan Masyarakat, TBM). This study seeks to explore the efforts of TBM Al-Istiqomah to enhance children's interest in reading in Cileunyi Kulon Village, Bandung Regency. The research employs a qualitative approach conducted at TBM Al-Istiqomah, Cileunyi Kulon, Bandung Regency, from January to April 2023. Data collection techniques include observation, interviews, and documentation. Data analysis follows the stages of data reduction, data presentation, and conclusion drawing. The findings reveal that TBM Al-Istiqomah has implemented various strategies to improve reading interest among primary school-aged children, such as providing engaging reading materials, organizing appealing and interactive literacy activities, and collaborating with PKBM institutions and other non-formal educational organizations. However, several supporting factors and challenges have been identified in these efforts, including limited funding for development, a lack of human resources, and difficulties in establishing partnerships with local government authorities